2016
DOI: 10.1039/c6ra22719h
|View full text |Cite|
|
Sign up to set email alerts
|

Green synthesis of 1,4-benzodiazepines over La2O3 and La(OH)3 catalysts: possibility of Langmuir–Hinshelwood adsorption

Abstract: Adsorption of all the reactants and order of addition play a key role in the synthesis of 1,4-diazepines depicting possibility of Langmuir–Hinshelwood mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
(53 reference statements)
3
14
0
Order By: Relevance
“…In the following reasonable mechanism for the above-mentioned reaction ( Scheme 3 ), La 2 O 3 nanoparticles acted as a Bronsted base [ 10 , 11 ] which deprotonated the active methylene group of malononitrile dimer ( 1 ) and gave the respective anion intermediate A . The latter carbanion attacked the β-carbon of enaminone ( 2a – h ) with displacement of dimethylamine, as a good leaving group, to give the non-isolable intermediate B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following reasonable mechanism for the above-mentioned reaction ( Scheme 3 ), La 2 O 3 nanoparticles acted as a Bronsted base [ 10 , 11 ] which deprotonated the active methylene group of malononitrile dimer ( 1 ) and gave the respective anion intermediate A . The latter carbanion attacked the β-carbon of enaminone ( 2a – h ) with displacement of dimethylamine, as a good leaving group, to give the non-isolable intermediate B .…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, lanthanum oxide (La 2 O 3 ) nanoparticles have shown considerable basic properties that adapt to many base catalyzed reactions [ 10 , 11 ]. Unfortunately, some difficulties limit its use, such as its difficult separation and reusability since the used catalyst could not be quantitatively recovered and the purification of the products being the biggest challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lanthanide compounds, such as La 2 O 3 and La(OH) 3 diffraction peaks were not observed for P-LM3, P-LM6, P-LM9, and P-LM12 samples, which was due to the low content of the La element. Nano-sized La 2 O 3 has been synthesized by SCS in earlier studies [24,25,26]. Gangwar et al [24] reported that a pure La 2 O 3 phase can be synthesized by SCS followed by calcination treatment, while La 2 O 3 converts to La(OH) 3 upon exposure to the atmosphere due to its hygroscopic nature.…”
Section: Resultsmentioning
confidence: 99%
“…37-1493) [22]. The orthorhombic structure peaks are located at 24.02 [23] phases are observed, and La 2 O 3 and La(OH) 3 exhibit hexagonal structures [24]. The peaks corresponding to La(OH) 3 are 39.36 • and 43.46 • , while the peaks of La 2 O 3 are 62.44 • and 64.02 • .…”
Section: Phase and Morphology Analysesmentioning
confidence: 94%